2021
DOI: 10.1038/s42003-021-02445-y
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in mechanical unfolding of protein upon partner-assisted pulling and handle-assisted pulling

Abstract: Proteins as force-sensors respond to mechanical cues and regulate signaling in physiology. Proteins commonly connect the source and response points of mechanical cues in two conformations, independent proteins in end-to-end geometry and protein complexes in handshake geometry. The force-responsive property of independent proteins in end-to-end geometry is studied extensively using single-molecule force spectroscopy (SMFS). The physiological significance of the complex conformations in force-sensing is often di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…linker between EC2-3 domains, there also we observed that the linker is pre-compressed (Figure S9a) . Further, the ∼12 nm extension, referring as partial domain unfolding(Arora et al, 2021), may diffuse force non-elastically and could be the dashpots in the spring. Notably, a gating-spring by definition, must possess elastic and non-elastic (dashpot) compliances.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…linker between EC2-3 domains, there also we observed that the linker is pre-compressed (Figure S9a) . Further, the ∼12 nm extension, referring as partial domain unfolding(Arora et al, 2021), may diffuse force non-elastically and could be the dashpots in the spring. Notably, a gating-spring by definition, must possess elastic and non-elastic (dashpot) compliances.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic alterations in the entropic conformations of the extraordinarily long tip-links cadherins under tension are already reported (Arora et al, 2021;Bartsch et al, 2018;Choudhary et al, 2020;Oroz et al, 2019). How such alterations contribute to the bond-lifetime dynamics of tip-links is not yet clear.…”
Section: Unfolding Mediated Unbinding Controls the Force-disseminatio...mentioning
confidence: 98%
See 3 more Smart Citations